Income and Expenditure of the Polish Population in 2006 (An analysis of Regional Diversification) - Parysek, Jerzy; Mierzejewska, Lidia (Bulletin of Geography. Socio-economic Series, 2010)
Changes in the political system after 1989 have led to the opening up of new areas of study in many fields of research, including socio - economic geography. One such example, undoubtedly, is the regional diversification of income and expenditure of the population, which was the subject of the ongoing studies, whose selected results are presented in this study. An analysis of the level of income and expenditure of the population was important, as it provided information on: the level of socio-economic development, the standard of living, the level of civilization and culture development, consumption structures, consumption patterns, changes in the structure of demand, etc. Therefore, it was significant for understanding the process of changes which have taken place in Poland. The analysis also provided new generic approaches (problems). This article presents, above all, the research results of the regional diversification of income and expenditure levels as well as the consumption structures of the Polish population in 2006 (in an elementary, complex and synthetic section). A further aim of the research, was to determine statistically significant factors which influence the income and consumption patterns - both factors which had a positive impact (the level of urbanization, the efficiency and productivity of the economy, agricultural produce) and a negative one (unemployment, age structure of the population, population growth and industrial production). This resulted from the conviction that, each description is valuable only if it is supplemented with an explanation of the reasons for such a state of affairs.